The Role of Women in Public Life According to Islamic Values and Banyumas - Ariyanti, Vivi (Transformatif, 2024)
The significance of women in public life rises as Indonesia embarks on reforming its political institutions and processes due to democratization. This study examines women's public life in Banyumas Regency, Central Java, in the context of cultural and Islamic values. Both Islamic and Penginyongan cultural values endorse traditional gender roles, potentially limiting women's public participation. However, these values also foster social harmony, community involvement, and religious ethics, which may support women's political engagement. The research data includes the number of women in public roles, their effectiveness in advocating for women's interests, and the interpretation of Islamic and Penginyongan cultural values. Data collection methods encompass interviews, observations, and document analysis. This study concludes by utilizing a sociological approach based on David Easton's systems theory that Islamic and Penginyongan cultural values influence women's public life, and political representation in Banyumas is multifaceted and shaped by various interacting factors. Understanding these dynamics is essential for crafting strategies to advance gender equality and women's public life empowerment in the region.